THE INFLUENCE OF TERRAIN ALTITUDE, SLOPE EXPOSURE AND SLOPE DEGREE ON PLANT SPATIAL DISTIRIBUTION - Sokolova, G. G. (Acta Biologica Sibirica, 2016)
Article represents the state-of-the-art review of the literature considering influence of a relief on a spatial distribution of separate plants and vegetable communities. The relief is the ecological factor exerting indirect impact on a vegetable cover due to redistribution of heat, light and moisture. The author allocated ecologically significant elements of a relief – district height above sea level, an exposition of a slope and the steepness of a slope. Explicitly influence of height of the district above sea level on different forms of a relief – a macrorelief, a mesorelief, and a microrelief are considered. It is noted that in mountain systems vegetation it is more rich and more various than vegetation of plains that is caused by large variety of soil climatic conditions in mountains. Height of separate belts and a set of species of plants in them depend on the mountains latitude. Fluctuation of temperature gradient concerning the heights, seasons, and slopes of different exposition is very large. The mesorelief and microrelief caused the redistribution of heat and moisture, and also nutrients in the soil. For such forms of a relief the altitude change of a vegetable cover is extremely poor. In the conditions of meso - and a microrelief there is an increase in fluctuation of temperatures, intensity of frosts, duration of the frost-free period that generally influences the development of plants, their abundance and spatial distribution. Radiation level, winter distribution of snow and speed of wind depend on slope exposure. On slopes of different exposures some natural changes of air and soil temperature are observed. Exposure of slopes are of great importance for the life cycle of plants. Influence of various slope exposures is reflected in structure of vegetation on all the forms of a relief. Distinctions in soil temperatures on the slopes with various exposures also affect air temperature that is reflected in character of vegetation, structure of flora, dynamics of vegetation development and morphology of plants. Temperature of the soil and ground air layer, thickness of snow cover, size of daily amplitude of temperature, power of a soil profile, intensity of an erosion depends on the degree of slope. The degree of slope influences the specific structure and structure of phytocoenosis, emergence the petrophylous bush species, semi-low shrubs and grassy plants, formation of ecological, genetic and altitudinal zones of vegetable communities.